Teaching Factory Management in the Hospitality Sector in Improving the Quality of Vocational High School Graduates - Syaiful Mujab; Hanafiah, Hanafiah; Teti Ratnawulan; Ida Tejawiani (Journal of Science and Education (JSE), 2025)
his study analyzes the management of teaching factory programs in the hospitality sector to improve the quality of vocational high school graduates, which has not been optimal across planning, organizing, implementation, and supervision. Using George R. Terry’s management theory and a qualitative case study approach, data were collected through observation, interviews, and documentation. The findings reveal: (1) Planning has been well-executed, focusing on goal setting, competency strategies, teaching module preparation, and facility analysis; (2) Organizing involves systematic determination of personnel, infrastructure, and student roles, aligned with industrial needs and school regulations; (3) Implementation follows established standard operating procedures to ensure competency-based training; and (4) Supervision includes ongoing monitoring and evaluation to ensure alignment with plans and promote continuous improvement. Overall, teaching factory management has contributed to graduate competency development aligned with the Indonesian National Work Competency Standards (SKKNI) and industry demands. Key supporting factors include professional human resources, adequate facilities, student involvement, and support from the government and industry sectors.